HUBUNGAN ANTARA PENGETAHUAN DAN KEBIASAAN MENGKONSUMSI FAST FOOD DENGAN STATUS GIZI PADA REMAJA - T. Syarifah Latifah Hanum; Ari Pristiana Dewi; Erwin ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this research is to identify the correlation between knowledge and habit of consuming fast food with nutrition status in teenage. This research used a cross sectional design. The sample was 83 teenage were taken by using technique of proportionate stratified random sampling. The measuring instrument used was questionnaire as its measure system which was designed by the researcher herself and has been proven by using validity and reliability tests. The analyses of this research were univariate and biavariate analysis by using Chi Square test. The result showed knowledge on nutrition status was obtained p value > alpha (ρ0,80>α 0,05), so it was got no significant correlation between fast food and nutrition status in teenage. Type of the most frequently consumed fast food was non-traditional fast food (55,4%), there was no significant relation between. The frequency of fast food consumption and nutrition status in teenage (ρ0,347>α 0,05). Frequency of eating fast food are in the category of frequent (55,4%), there was a significant association between the frequency of fast food consumption and nutrition status in teenage p value < alpha (ρ0,029<α 0,05). Based on this research, researcher suggested that teenage had a better concern and able to choose food that is safe for consumption. Keyword: fast food, habits, knowledge, teens